2018
DOI: 10.1038/s41581-018-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

HLA and kidney disease: from associations to mechanisms

Abstract: Since the first association between HLA and diseases of native kidneys was described almost 50 years ago, technological and conceptual advances in HLA biology and typing, together with better case ascertainment, have led to an improved understanding of HLA associations with a variety of renal diseases. A substantial body of evidence now supports the existence of HLA genetic associations in the field of renal disease beyond the role of HLA in allogeneic responses in transplant recipients. Allomorphs of HLA have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 188 publications
(213 reference statements)
0
60
1
Order By: Relevance
“…In the majority of the previous works, ESRD patients waiting for kidney transplantation were examined. Nonetheless, there are several contradictions in these studies, and no consistent trend on the association between different HLA alleles and ESRD was observed [1]. It has been suggested that a few HLA alleles may affect the severity of kidney disease or risk of progression [1].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the majority of the previous works, ESRD patients waiting for kidney transplantation were examined. Nonetheless, there are several contradictions in these studies, and no consistent trend on the association between different HLA alleles and ESRD was observed [1]. It has been suggested that a few HLA alleles may affect the severity of kidney disease or risk of progression [1].…”
Section: Introductionmentioning
confidence: 94%
“…Nonetheless, there are several contradictions in these studies, and no consistent trend on the association between different HLA alleles and ESRD was observed [1]. It has been suggested that a few HLA alleles may affect the severity of kidney disease or risk of progression [1]. For instance, specific HLA alleles could promote a more generalized pro-fibrogenic T cell phenotype that may contribute to disease progression or onset [1].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Presentation of alloantigen's is a central path mechanism of alloimmunity and involves MHC class II molecules on professional antigen-presenting cells (Borges et al, 2016;Robson et al, 2018). Within antigen-presenting cells, the maturation of MHC class II molecules is tightly regulated, whereby the invariant chain covers the peptide-binding domain up to when peptide loading occurs and the molecule is shuttled to the cell surface (Roche and Frusta, 2015;Robson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Presentation of alloantigen's is a central path mechanism of alloimmunity and involves MHC class II molecules on professional antigen-presenting cells (Borges et al, 2016;Robson et al, 2018). Within antigen-presenting cells, the maturation of MHC class II molecules is tightly regulated, whereby the invariant chain covers the peptide-binding domain up to when peptide loading occurs and the molecule is shuttled to the cell surface (Roche and Frusta, 2015;Robson et al, 2018). Cathepsin (Cat-) S is one of several proteases that chop the invariant chain in a stepwise process (Shi et al, 1999;Roche and Frusta, 2015); hence, Cat-S deficiency or pharmaceutical Cat-S inhibition prevents MHC class II-mediated (auto)antigen presentation (Rise et al, 1996(Rise et al, , 1998Dresden et al, 1999;Saugus et al, 2002;Stickle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%